2020
DOI: 10.3847/1538-4357/abb883
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation Amplitudes of Magnetic-field Directional Turnings and Magnetic-velocity Alignment Structures in the Solar Wind

Abstract: Magnetic-field directional turning (MFDT) and magnetic-velocity alignment structure (MVAS) are two typical types of structures in the solar wind. However, their fluctuation amplitudes in different turbulence states have not been studied before. Here, we present the amplitude distributions of MFDTs and MVASs in the plane, where is the correlation coefficient between magnetic-field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In the region between the two sub-Alfvénic flows, PSP observed possible partial HCS crossings, where the magnetic field magnitude |B| decreases to near zero but without direction changes in the radial magnetic field B R . Low values of the normalized cross-helicity σ c and highly negative normalized residual energy σ r are observed near the partial HCS crossings, which are consistent with previous observations (Zhao et al 2021c) and suggest the presence of convected solar wind structures with near-zero velocity fluctuations (e.g., Tu & Marsch 1991;Wang et al 2020;Zhao et al 2020). 2.…”
Section: Discussionsupporting
confidence: 88%
“…In the region between the two sub-Alfvénic flows, PSP observed possible partial HCS crossings, where the magnetic field magnitude |B| decreases to near zero but without direction changes in the radial magnetic field B R . Low values of the normalized cross-helicity σ c and highly negative normalized residual energy σ r are observed near the partial HCS crossings, which are consistent with previous observations (Zhao et al 2021c) and suggest the presence of convected solar wind structures with near-zero velocity fluctuations (e.g., Tu & Marsch 1991;Wang et al 2020;Zhao et al 2020). 2.…”
Section: Discussionsupporting
confidence: 88%
“…We also notice that in this case the fluctuation amplitude of the proton velocity is much smaller than the magnetic field (normalized residual energy σ r = −0.91), and the fluctuations between the velocity and the magnetic field are not well correlated (correlation coefficient cc = −0.11). These characteristics indicate that this case may be associated with magneticfield directional turning (Tu and Marsch, 1991;Wang et al, 2020). It is convected by the solar wind, and nearly has no velocity fluctuations.…”
Section: Methodsmentioning
confidence: 83%
“…The nature of these fluctuations needs further study. A candidate may be the magnetic structures, reported by Wang et al (2020). The magnetic-velocity alignment structures may have a flux-tube texture (Borovsky 2020), which are possible remnants of coronal jets (Sterling & Moore 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Tu et al (2016) presented the first two time series with high C vb values and low r A values, and suggested that these time series may represent convecting magnetic field structures in the solar wind. Wang et al (2020) first suggested the concept of magnetic-velocity alignment structures. They are magnetically dominated structures with high correlation between magnetic field fluctuations and velocity fluctuations-MVAS, of which C 0.8 0.9 vb -and 0.9 0.2 r ( ) ( ) s~---.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation